Exhaustive Analysis of the Study of Antiretroviral Adherence Factor From HIV/AIDS Patients - Alfitri Alfitri; Neviyarni Neviyarni; Firman Firman; Netrawati Netrawati; Rihaliza Rihaliza; Mahalul Azam; Elsa Yuniarti (Jurnal Kesehatan Masyarakat, 2025)
Adherence of HIV/AIDS patients in ARV therapy is an important factor in the success of HIV/AIDS treatment because continuous ARVs can suppress the development of the virus, reduce viral resistance, improve the HIV/AIDS patient's quality of life, and improve their health in general. This study aimed to review the literature that has researched factors related to the non-adherence of HIV/AIDS patients in taking ARV therapy. The research conducted an empirical analysis related to the aspects of adherence of HIV/AIDS patients to antiretroviral therapy (ART).  A total of 71 kinds of literature discusses the adherence of patients with HIV/AIDS to treatment with ARVs. Literature was obtained based on searches on the Scopus website for the year 2019-2023. The literature is dominant in 2019 and has decreased over time. The publication is predominantly in Q1-indexed journals, with the first author coming from the USA. General factors that become ART adherence based on the literature include finance, mental health, alcohol consumption, drug abuse, belief, self-efficacy, knowledge, homeless, support, and tobacco/smoking. The most commonly encountered factors are support and mental health. The further suggestions for medical personnel or patients with HIV/AIDS and their families to be more synergistic in carrying out medical therapy.